Salmonella spp. detection in fresh and freeze-dried frog meat: a comparison of methods - Mello, Silvia Conceição Reis Pereira; DE SOUZA, Rossiane M.; Rodrigues, Eliane; Caracuschansk, Fernando David [UNESP]; Mendes, Beatriz V.; DE MESQUITA, ELIANA DE FÁTIMA M. (FapUNIFESP (SciELO), 2025)
This study examined the presence of Salmonella spp. in fresh frog meat and freeze-dried seasoned frog meat stored for up to 90 days at room temperature. The samples were analyzed in triplicate using the conventional official method, by polymerase chain reaction (PCR) and mass spectrometry technique (MALDI –TOF) — for a comparison of the results obtained by the three tested methods. Mass spectrometry analyses confirmed the presence of Salmonella spp. in 100% of the fresh frog meat samples. In the analysis by the conventional method, the percentages of detection were 67% and 100% in samples B2 and B3, whereas the PCR method indicated 100% and 67% presence of the bacteria in the respective samples. In the analyses of freeze-dried none of the three methods detected the presence of Salmonella spp. The different analysis methods tested in this study were efficient in determining the presence or absence of Salmonella spp. in the samples, and the comparison between methods revealed a high percentage of compatibility of results. Adoption of efficient detection methods, such as PCR and MALDI-TOF, is essential, not only for public health, but also for compliance with Brazilian regulations, ensuring that food products are free from Salmonella spp. contamination and safe for consumption.
Keywords: Aquarana catesbeiana; MALDI-TOF; microbiological analysis of foods; poly-merase chain reaction